2020
DOI: 10.30534/ijatcse/2020/9891.12020
|View full text |Cite
|
Sign up to set email alerts
|

The Association between the Effectiveness of Human Resource Management Functions and the Use of Artificial Intelligence

Abstract: The main purpose of this study is to investigate the association between the effectiveness of human resource management (HRM) functions and the use of artificial intelligence (AI). The HRM functions included in this research are recruitment and selection, people analytics, and talent acquisition. A quantitative research design was used in this study. A questionnaire containing 30 questions was prepared and submitted to employees and managers working in companies in three major cities (Riyadh, Jeddah, and Damma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Case in point, data stored in cloud platforms like HRIS (HR Information Systems) are composed of information on employee's demographic information (employment history, skills and competencies, formal educational qualifications and demographic information) alongside softer performance data that might be collected at appraisals and performance reviews (Angrave et al, 2016). In this context, AI-driven HR analytics has emerged as a popular research area within HRM (Baakeel, 2020), leveraging datasets stored in HRIS. It allows to redefine the way companies will manage their workforce (Giermindl et al, 2021), particularly to have a proficient workforce (i.e., suitable skills, expertise and experience) required to succeed in the organizations (Singh and Malhotra, 2020;Sivathanu and Pillai, 2018).…”
Section: Ai Applicationsmentioning
confidence: 99%
“…Case in point, data stored in cloud platforms like HRIS (HR Information Systems) are composed of information on employee's demographic information (employment history, skills and competencies, formal educational qualifications and demographic information) alongside softer performance data that might be collected at appraisals and performance reviews (Angrave et al, 2016). In this context, AI-driven HR analytics has emerged as a popular research area within HRM (Baakeel, 2020), leveraging datasets stored in HRIS. It allows to redefine the way companies will manage their workforce (Giermindl et al, 2021), particularly to have a proficient workforce (i.e., suitable skills, expertise and experience) required to succeed in the organizations (Singh and Malhotra, 2020;Sivathanu and Pillai, 2018).…”
Section: Ai Applicationsmentioning
confidence: 99%
“…According to Tambe et al (2019), using AI enables a number of predictive tasks for hiring, choosing, onboarding, training, performance management, promotion, keeping employees and providing rewards to them. Baakeel (2020) specifically looked at the use of AI in recruiting and saw the possibility of speedy resume screening, prompt and automatic responses to candidate inquiries and virtual recruitment activities. Yang et al (2017) utilized machine learning to develop a precise and cost-efficient job recommendation system.…”
Section: Hr Functionsmentioning
confidence: 99%
“…Peisl and Edlmann (2020) investigated the factors related to the acceptance and use of Predictive HRA and concluded that the attitude of executives is the most significant one. Meanwhile, Singh and Malhotra (2020) and Baakeel (2020) found that the technological background of the organization is the main factor that impacts implementation of innovations in the HRD. Finally, McCartney et al (2020) emphasized consulting, technical expertise, data analysis skills, human capital and business intellectual capital as crucial for HRA adoption.…”
Section: Human Resource Analytics (Hra)mentioning
confidence: 99%